Unusual Biliary Complication in the Modern Surgical Century: Bouverets Syndrome (Global Journal of Medical Research, 2020)
Background: Bouveret's syndrome is a rare type of gallstone ileus. It consists of duodenal obstruction secondary to the passage of a stone through afistula established between the gallbladder and the duodenum. Case Presentation: Here in, we report the case ofa 60-year-old female patient who presented dyspepsia with vomiting of solids and liquids foods in the preceding weeks. Severe dehydration and asthenia concomitant. The examination showed epigastric pain with tympanic percussion. Laboratory: mild leukocytosis and hypokalemia. MRI:an image of 34 x 56 mm endoluminal hypointense is observed in duodenal compatible with biliary lithiasis. A suspicion of a fistula between the gallbladder and the duodenum was considered. Conclusion: Bouveret's Syndrome is rare, so the diagnosis is of exclusion. The ideal treatment is endoscopic, but if this route fails, surgery is necessary, prioritizing the mini-invasive approach.
Keywords: bouveret's syndrome; fistula; gallstone ileus; mini-invasive approach; duodenal obstruction; enterolithotomy